Seroprevalence of anti-SARS-CoV-2 IgG in asymptomatic and pauci-symptomatic people over a 5 month survey in Argentina - Rodeles Antonelli, Luz María (2021)
Objective. To evaluate the seroprevalence of COVID-19 infection in pauci-symptomatic and asymptomatic people, the associated epidemiological factors, and IgG antibody kinetic over a 5-month period to get a better knowledge of the disease transmissibility and the rate of susceptible persons that might be infected. Methods. Seroprevalence was evaluated by a cross-sectional study based on the general population of Santa Fe, Argentina (non-probabilistic sample) carried out between July and November 2020. A subgroup of 20 seropositive individuals was followed-up to analyze IgG persistence. For the IgG anti-SARS-CoV-2 antibodies detection, the COVID-AR IgG® ELISA kit was used. Results. 3 000 individuals were included conforming asymptomatic and pauci-symptomatic groups (n=1 500 each). From the total sample, only 8.83% (n=265) presented reactivity for IgG anti-SARS-CoV-2. A significant association was observed between positive anti-SARS-CoV-2 IgG and a history of contact with a confirmed case; the transmission rate within households was approximately 30%. In the pauci-symptomatic group, among the seropositive ones, anosmia and fever presented an OR of 16.8 (95% CI 9.5-29.8) and 2.7 (95% CI 1.6-4.6), respectively (p <0.001). In asymptomatic patients, IgG levels were lower compared to pauci-symptomatic patients, tending to decline after 4 months since the symptoms onset. Conclusion. We observed a low seroprevalence, suggestive of a large population susceptible to the infection. Anosmia and fever were independent significant predictors for seropositivity. Asymptomatic patients showed lower levels of antibodies during the 5-month follow-up. IgG antibodies tended to decrease over the end of this period regardless of symptoms.